Informatics in comprehensive schools: changes and problems - Dagienė, Valentina (Lietuvos matematikos rinkinys, 1998)
This paper deals with Informatics teaching in Lithuanian comprehensive schools. The main attention is paid to the analyses of compulsory course of Informatics.The Informatics became obligatory in all Lithuanian secondary schools (in 10th and 11th grade) more than ten years ago. Since next school year the Informatics will be a compulsory course in the final years of the basic school (9th and 10th grade). Recently the Informatics syllabus of basic schools embraces four main topics: information, algorithms, computers, and information technology. Some remarks on Informatics syllabus and standards are presented.